2016
DOI: 10.18488/journal.68/2016.3.4/68.4.64.73
|View full text |Cite
|
Sign up to set email alerts
|

Village Chicken Production and Marketing in West Gojjam Zone, Ethiopia

Abstract: Chicken production in West Gojjam zone was characterized by using indigenous chicken with low input-output level. Despite its diverse socio economic role for smallholder farmers, production and productivity of village chicken was very low. As the result, chicken producers were not benefited from the sector. Therefore, this study was conducted with the aim of characterizing chicken rearing practice, flock dynamics and determining the off-take rate of village chicken production system. It was conducted in West G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Previous research has shown that "women use the money earned from selling poultry products for a variety of purposes." They buy food (e.g., spices or cooking oil), clothing, and medical care (both modern and traditional), as well as school fees and school supplies such as books and pens for their children (Assefa and Tolemariam, 2015). This was in the same line with the findings of the current study where the respondents were strongly agreed (41.7%) that income from the poultry products made farmers afford payment of health services, afford payment of education services (40.8%), payment of tax base (43.7%), increased Resilience (37.9%) and gaining of land, buildings, and house equipment's (40.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that "women use the money earned from selling poultry products for a variety of purposes." They buy food (e.g., spices or cooking oil), clothing, and medical care (both modern and traditional), as well as school fees and school supplies such as books and pens for their children (Assefa and Tolemariam, 2015). This was in the same line with the findings of the current study where the respondents were strongly agreed (41.7%) that income from the poultry products made farmers afford payment of health services, afford payment of education services (40.8%), payment of tax base (43.7%), increased Resilience (37.9%) and gaining of land, buildings, and house equipment's (40.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Its elevation varies from 1500 to 3500 m.a.s.l. Most of the districts (75%) in the zone have ambient temperature ranging from 15 to 200°C, and the remaining (17%) have 20–270°C [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in the West Gojjam zone, North West of Ethiopia particularly in Javitenan, North Achefer, and Bahir Dar Zuria districts in which practice, distribution, and use of medicinal plants and animals are high. West Gojjam zone is one of the 10 zones in the Amhara Region and lies between 36° 30' to 37° 5' Longitudes East and 10°16' to 11°54' Latitudes North [20]. The total population is estimated as 2,106,596 and more than 91% of the people lived in rural areas [21].…”
Section: Description Of the Study Area I Locationmentioning
confidence: 99%